Sistem Pengambilan Keputusan Mengunakan Metode Ahp Untuk Menentukan Siswa Yang Berperilaku Menyimpang Dari Pengaruh Internet (Studi Kasus Smp Negeri 17 Padang) - Yusman, Yanti (STKIP PGRI Sumatera Barat, 2016)
The role of Internet technology rapidly advancing education among a lot of the gains due to the presence of the Internet makes it easy to search the subject matter , but there are also some boys and girls who misuse the internet therefore the authors are interested in completing these cases the extent of the role the Internet for students and girls in school after field research there are several answers of boys and girls in schools used the Internet to answer Nonto vidio porn , pornography stored and mature discussion so to answer this writer is interested to know the deviant behavior among male and female students of the school.Kata Kunci: Sistem, keputusan, AHP, internet